Identification and analysis of video subsequence using bipartite graph matching - Guimarães, Silvio Jamil F.; Patrocínio Jr., Zenilton Kleber G. do (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2010)
Subsequence identification consists in identifying real positions of a specific video clip in a video stream together with the operations that may be used to transform the former into a subsequence from the latter. To cope with this problem, we propose a new approach considering a bipartite graph matching to measure video clip similarity with a target video stream which has not been preprocessed. We show that our approach locates edited video clips allowing insertion, removal and replacement operations. Experimental results demonstrate that our method performance achieve 93% recall with 93% precision, though it has a low computational cost since its classifications step is extremely simple.